Distinct Roles of IL-1β and IL-18 in NLRC4-Induced Autoinflammation - Sasaki, Yuki; Otsuka, Kunihiro; Arimochi, Hideki; Tsukumo, Shin-Ichi; Yasutomo, Koji (Frontiers in Immunology, 2020)
NLRC4 acts as an intracellular sensor to detect bacterial invasion, and NLRC4 activation leads to the production of IL-1β and IL-18 together with pyroptosis-mediated cell death. Missense active mutations in NLRC4 cause autoinflammatory disorders whose symptoms are distinctly dependent on the site of mutation and other aspects of the genetic background. To determine the involvement of IL-1β and IL-18 in the inflammation induced by NLRC4 mutation, we depleted IL-1β, IL-18 or both cytokines in Nlrc4-transgenic mice in which the mutant Nlrc4 is expressed under the MHC class II promoter (Nlrc4-Tg mice). The deletion of the Il1b or Il18 gene in Nlrc4-Tg mice reduced the neutrophil numbers in the spleen, and both deletions led to an equivalent number of neutrophils compared to wild-type mice. The deletion of Il1b ameliorated but did not eliminate the hyperplasia of bone marrow, while mice deficient in Il18 showed no bone marrow hyperplasia. In contrast, tail bone deformity remained in the presence of Il18 deficiency, but Il1b deficiency completely abolished bone deformity. The decreased bone density in Nlrc4-Tg mice is counteracted by Il1b but not Il18 deficiency. Our results demonstrate the distinct effects of IL-1β and IL-18 on NLRC4-induced inflammation among tissues, which suggests that blockers for each cytokine should be utilized depending on the site of inflammation.